Energy system analysis, simulation and modelling practices in Turkey - (:unkn) unknown (Springer, 2020)
Humankind first began to use simple machines instead of arm force. Subsequently, more advanced and sophisticated energy technologies introduced to our lives since the industrial revolution. Relatively advanced machines have begun to replace the simple mechanical systems in order to meet the various needs of humanity. Continuous improvements in related technologies have triggered the emergence of more compact, modular and more efficient vehicles over time. The rapid advances in technology naturally manifested itself also in energy technologies. Drivers in a national economy, particularly environmental problems caused by energy production and consumption, have been an area of interest in recent years. Energy technologies include increasing productivity, producing relatively more energy, or working towards an upward trend. In this perspective, this chapter aims to give an overview of the recent analysis of an energy system and modelling studies conducted by the energy joint workgroup at Marmara University and Naval Academy of National Defence University, Istanbul, Turkey. © Springer Nature Switzerland AG 2020.
Keywords: Energy modelling; Energy system analysis; Turkey